2020
DOI: 10.1177/2042018820937217
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal glycemic control among subjects with diabetes mellitus in India: a subset analysis of cross-sectional wave-7 (2016) data from the International Diabetes Management Practices Study (IDMPS)

Abstract: Objective: To assess the real-world management practices of subjects with type 2 diabetes mellitus (T2DM) and type 1 diabetes mellitus (T1DM) in India. Methods: This cross-sectional study was conducted between 7 March 2016 and 15 May 2016 in India as part of the seventh wave (2016) of the International Diabetes Management Practices Study (IDMPS). Adult subjects with T1DM or T2DM visiting physicians during a 2-week recruitment period were included. Results: A total of 55 physicians included 539 subjects who met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
3
3
0
Order By: Relevance
“…These observations comprehensively portray a real-world picture of low glycemic control among participants with T2DM from India. These observations are in concordance with the previous evidence from India wherein uncontrolled glycemia was highlighted as a key feature of people with T2DM in India [ 32 34 ]. These results are further substantiated by a real-world cross-sectional study by Ramachandran et al wherein only 25.2% of participants with T2DM achieved glycemic control (HbA1c < 7%).…”
Section: Discussionsupporting
confidence: 93%
“…These observations comprehensively portray a real-world picture of low glycemic control among participants with T2DM from India. These observations are in concordance with the previous evidence from India wherein uncontrolled glycemia was highlighted as a key feature of people with T2DM in India [ 32 34 ]. These results are further substantiated by a real-world cross-sectional study by Ramachandran et al wherein only 25.2% of participants with T2DM achieved glycemic control (HbA1c < 7%).…”
Section: Discussionsupporting
confidence: 93%
“…This result is similar to that of the TIGHT (The Investigation of Glycosylated Haemoglobin on Therapy in Indian diabetics) study (23.4%) 15 and the International Diabetes Management Practices Study (IDMPS): wave-5 (2011)(2012)26.0% of participants from India had HbA1c < 53 mmol/mol or <7%) 16 and wave-7 (2016, 25.2% of participants had HbA1c 53 mmol/mol or <7%). 17 This result is also similar to that of a report from North Kerala (28.3%, HbA1c < 53 mmol/mol or <7%) 18 and to that of a recent national diabetes registry program conducted across 200 diabetes clinics/centers in India (23.4%). 19 Further, the 1st phase of the multicentric Indian Council of Medical Research-India Diabetes (ICMR-INDIAB) study conducted in 480 participants with selfdeclared diabetes reports a slightly higher (31.0%) proportion of participants with glycemic control.…”
Section: Discussionsupporting
confidence: 88%
“…At baseline, only 25.1% of the study population had optimal glycemic control (HbA1c < 53 mmol/mol; <7%). This result is similar to that of the TIGHT (The Investigation of Glycosylated Haemoglobin on Therapy in Indian diabetics) study (23.4%) 15 and the International Diabetes Management Practices Study (IDMPS): wave‐5 (2011–2012, 26.0% of participants from India had HbA1c < 53 mmol/mol or <7%) 16 and wave‐7 (2016, 25.2% of participants had HbA1c 53 mmol/mol or <7%) 17 . This result is also similar to that of a report from North Kerala (28.3%, HbA1c < 53 mmol/mol or <7%) 18 and to that of a recent national diabetes registry program conducted across 200 diabetes clinics/centers in India (23.4%) 19 .…”
Section: Discussionsupporting
confidence: 83%
“…Many studies have reported poor glycemic control in patients with T2D in South Asian countries. [3][4][5]. In India, the management of T2D is limited by the high burden and early onset of the disease [6].…”
Section: Introductionmentioning
confidence: 99%